Political PR in International Digital Communications: The Experience of the Eurasian Media Space - E. Yu. Kolobova (Евразийская интеграция: экономика, право, политика, 2024)
Digital media has become an integral part of the political life of citizens, as an increasing number of people around the world use digital media technologies for communication. Digital media contribute to the formation of socio-political factors that raise concerns about the spread of disinformation, information disagreements and political polarization.Aim. To analyze the tools, problems and opportunities of political PR in the context of digitalization of the media space in foreign countries and the EAEU countries.Tasks. To give significant ideas about the concepts of “political public relations” and “political communication”; to identify factors influencing political communication processes; to present international experience in the application of political PR in the context of digitalization of media; to formulate the possibilities for the development of Eurasian integration in the context of digitalization of the media space.Methods. The methodological basis of the scientific research was such modern general scientific research methods as: comparative analysis, statistical and structural-logical methods, content analysis of open sources of information.Results. The paper defines the role and importance of digital media in political PR activities, identifies traditional and modern factors of influence on political activity, as well as problems in the new digital reality. To build political communications with the audience, its impact and increase engagement, political organizations use new media technologies using multimodality. In practice, the digital inequality of the world population deprives a number of people of digital communication, and as a result, the necessary conditions for participation in the political and economic life of the country. The digital divide of the EAEU countries reduces the political communicative impact on citizens’ beliefs in the need to strengthen integration processes. It seems appropriate to introduce consistency in the formation of the Eurasian integration agenda and a single digital information field to increase the political culture of civic engagement in all EAEU member states.Conclusions. With the help of variation of resources, the necessary content is formed to create the necessary audience effect. Indeed, digital media has a number of advantages that have been proven in practice, however, political PR is influenced by the negative side of the development of digital communications — the spread of fake news, most of which cannot be traced to the source. Therefore, the transformation of digital opportunities, the distribution of political resources, the dissemination of political discourse and the structure of political opportunities in the digital age is the most relevant in the modern world. Using the example of the EAEU countries, it is proved that digitalization in the international media space causes the involvement of citizens of different countries in integration, generalization and formation of public support for the state.